Analisis Penyajian Laporan Keuangan Berdasarkan Peraturan Pemerintah Nomor 71 Tahun 2010 Pada Pengadilan Negeri Slawi Kelas I B - Fadhillah Subekti; Harjanti, Ririh; Aryanto, Aryanto (LPPM UBP, 2024)
Government Accounting Standards are accounting principles that are applied in prepareing government financial reports in transparent and accountable manner. Pengadilan Negeri Slawi Kelas I B is one of the accounting entities under Mahkamah Agung republic Indonesia which is obliged to carry out accounting and accountability reports on the implementation of state revenue and expenditure budget. The purpose of this research was to determine the presentation of financial statement based on PP No. 71 of 2010 at the Pengadilan Negeri Slawi Kelas I B. Methods of collecting data use in this research was observation, interview, and study of literature. The analysis method used is descriptive qualitative methode. The results of the research show that the components of the financial reports of the Pengadilan Negeri Slawi Kelas I B, namely Budget Realization Report, Balance Sheet, Operational Report, Changes of Equity Report, and Notes to Financial Statement has been appropriate besed on PP No. 71 of 2010. Nonethless, there are still posts in the Budget Realization Report that haas not been included.